Virtual Clay Prototyping System – A Framework for Real-Time Modeling - Bin, Qi; Ming, Sun Xiao; Eujin, Pei; Jian, Liu Bing (International Journal of Online and Biomedical Engineering (iJOE), 2015)
In order to provide users a real-time force-feedback immersive virtual modelling environment, powerful computing capabilities are often needed. As this potentially results in a calculation bottleneck, virtual modelling scenes are often delayed and resulting in a poor user experience. In this paper, the authors present a novel approach to improve the calculation speed for the volume pixel (voxel) amount of force feedback generated based on the amount of pressure exerted on the ‘virtual material’ per unit time. Results from the experiments reveal that this approach required less computing power, thereby offering a better user experience. This has been confirmed through a series of trials that investigated the amount of time students spent during sketching, physical modelling and virtual prototyping. Results found that the remapped virtual prototyping method was more effective than physical model in productivity in terms of time, and efficiency in terms of data conversion.